Аntibiotic resistance of bacterial cultures isolated from the feral pigeon (Columba livia) and starling (Sturnus vulgaris) at a solid waste landfill - Y. Y. Dementieieva; N. Muzyka; D. Muzyka; A. B. Chaplygina (Regulatory Mechanisms in Biosystems, 2022)
Resistance to antibiotics is well-known global phenomenon. There are places contributing to the development of antibiotic resistance such as waste landfills, especially ones that accept medical waste which did not undergo disinfection and livestock waste with bacteria not sensitive to antibiotics. An extensive system of transfer of antibiotic resistant microorganisms is formed on these territories (zoochory, groundwater, transport etc.). The aim of the research was to determine the species composition of bacteria isolated from birds of Derhachi municipal solid waste landfills in Kharkiv city, Ukraine. Also, we determine the sensitivity of bacterial isolates to a number of standard antibiotic drugs. We collected droppings of feral pigeons (Columba livia Gmelin, 1789; Columbidae) and starlings (Sturnus vulgaris Linnaeus, 1758; Sturnidae) during the winter period in 2020/2021; both species are dominants of waste landfills. We isolated 15 bacteria species of 4 families by bacteriological methods (growing on simple and selective media and identification by biochemical properties): Enterobacteriaceae (Enterobacter asburiae, E. dissolvens, E. cancerogenus, E. cloacae, E. sakazakii, Escherichia coli, Klebsiella terrigena, K. ornithinolytica, Citrobacter freundii, Proteus mirabilis), Yersiniaceae (Serratia ficaria, S. rubidaea, S. entomophila), Morganellaceae (Providencia stuartii) and Pseudomonadaceaе (Pseudomonas aeruginosa). Sensitivity was determined by the disk-diffusion method to 18 antibiotics. Ten isolates turned out to be multiresistant-resistant to three or more classes of antimicrobial drugs. A promising direction for future research is the determination of the pathogenicity of the isolates and checking the roles of birds of Derhachi solid waste landfills as reservoirs of pathogens. Currently, it can be assumed that large concentrations of synanthropic birds (especially those that forage on solid waste landfills) with a high probability are reservoirs of many bacteria, in particular those that have developed resistance to drugs.